Minimum acceptable diet among children aged 6-23 months in South Kivu, Democratic Republic of Congo: a community-based cross-sectional study - Richard Mbusa Kambale; Gaylord Amani Ngaboyeka; Joe Bwija Kasengi; Sarah Niyitegeka; Boss Rutakaza Cinkenye; Armand Baruti; Kizito Chentwali Mutuga; Dimitri Van der Linden (BMC, 2021)
Abstract Background Suboptimal child nutrition remains the main factor underlying child undernutrition in Democratic Republic of Congo (DRC). This study aimed to assess the prevalence of minimum acceptable diet and associated factors among children aged 6-23 months old. Methods Community-based cross-sectional study including 742 mothers with children aged 6-23 months old was conducted in 2 Health Zones of South Kivu, Eastern DRC. WHO indicators of Infant and Young Child Feeding (IYCF) regarding complementary feeding practices were used. Logistic regression analysis was used to quantify the association between sociodemographic indicators and adequate minimum acceptable diet for both univariate and multivariate analysis. Results Overall, 33% of infants had minimum acceptable diet. After controlling for a wide range of covariates, residence urban area (AOR 2.39; 95% CI 1.43, 3.85), attendance postnatal care (AOR 1.68; 95% CI 1.12, 2.97), education status of mother (AOR 1.83; 95% CI 1.20, 2.77) and household socioeconomic status (AOR 1.72; 95% CI 1.14, 2.59) were factors positively associated with minimum acceptable diet. Conclusion Actions targeting these factors are expected to improve infant feeding practices in South Kivu.